The impact of facilitation in a problem-based pedagogy on self-directed learning readiness among nursing students: a quasi-experimental study in Tanzania - Walter C. Millanzi; Patricia Z. Herman; Mahamudu R. Hussein (BMC, 2021)
Abstract Background Self-directed learning is important in nursing as it is associated with improved clinical and moral competencies in providing quality and cost-effective care among people. However, unethical professional conduct demonstrated by some graduate nurses is linked with the way they are developed in schools alongside the content and pedagogies prescribed in nursing curricula. Pedagogical transformations appear to be inevitable to develop enthusiastic nursing students who can work independently in delivering quality and cost-effective nursing services to people. This study intended to examine the impact of facilitation in a problem-based pedagogy on self-directed learning readiness among undergraduate nursing students in Tanzania. Methods A controlled quasi-experimental design was conducted in Tanzanian higher training institutions from January to April 2019. A 40-item Self-directed learning Readiness scale for nursing education adopted from previous studies measured self-directed learning and the Student A descriptive analysis via a Statistical Package for Social Sciences software program (version 23) was performed to establish nursing students' socio-demographic characteristics profiles. Independent samples t-test determined mean scores difference of self-directed learning readiness among nursing students between groups while regression analysis was performed to discriminate the effect of an intervention controlled with other co-related factors. Results The post-test results of self-directed learning readiness showed that nursing students scored significantly higher [(M = 33.01 ± 13.17; t (399) = 2.335; 95%CI: 0.486,5.668)] in the intervention group than their counterparts in the control. Findings of SDL readiness subscales were significantly higher among students in the intervention including self-management [(M = 10.11 ± 4.09; t (399) = 1.354; 95%CI: 0.173,4.026)], interest learning [(M = 9.21 ± 2.39; t (399) = 1.189; 95%CI: 0.166,4.323)] and self-control [(M = 13.63 ± 5.05; t (399) = 2.335; 95%CI: 0.486,5.668)]. The probability of nursing students to demonstrate self-directed learning readiness was 1.291 more times higher when exposed to the intervention (AOR = 1.291, p < 0.05, 95%CI: 0.767, 2.173) than in the control. Conclusion Facilitation in a problem-based pedagogy promises to change the spectrum of nursing learning habits potentially to their academic and professional achievements. Nurse tutors need to be empowered with it to prepare nursing students to meet their academic and professional potentials.